Conflicts as a Result of Land Measurement Errors Case Study: Land Ownership of the Former Mayor of Semarang - Sudjito Sudjito; Tatit Hariyanti; Labib Muttaqin; Hengki Firmanda; Rosa Nikmatul Fajri (Universitas Muhammadiyah Purwokerto, 2024)
This study explores a case that occurred on land owned by the former mayor of Semarang, Sukawi Sutarip. On land, land measurement errors occur and land ownership overlaps with other people's ownership. Conflicts between adjacent landowners were inevitable. This study aims to determine the chronology of the conflict, the causes of land measurement error and the legal consequences. This research is juridical-normative in nature, meaning that the truth of statements is measured based on positive legal norms. The data analysed is limited to secondary data collected from the internet. Data were analysed qualitatively. The results showed that it was true that there were errors in land measurement and the main causal factor was due to unprofessional officers; and give rise to legal conflict in the court. The legal consequence is that the certificate becomes legally and administratively flawed.Keywords: Conflict, Land, measurement, administrative flaw